Estimation of the biodegradability potential of bacterial isolated from a gas flare polluted soil in Ologbo settlement, Edo State, Nigeria - Jimmy Emejulu, Michael; Ugueri, Udochukwu; I., Atuanya E.; Ogochukwu, Osulu Emmanuel; Claribel, Chikezie Chidimma (Brazilian Journal of Biometrics, 2026)
Gas flaring is the most common source of global warming, causing environmental pollution and ecological disturbances. This study evaluated the environmental impact of gas flaring and possible bacterial isolates that can be employed in the remediation of petroleum hydrocarbon polluted soil. Soil samples collected from Ologbo Settlement in Edo State, Nigeria were analyzed for their physicochemical and petroleum hydrocarbon parameters. The Shake flask biodegradation test was carried with screening of hydrocarbon degrading bacterial isolates which were characterized using the 16S RNA analysis technique. Across the six locations (40, 80, and 120, 160, 200 and 1000 m) sampled from 40m to 1000m and the control, it was observed that there was a progressive increase in the soil pH, moisture content and electricity conductivity. In the other hand, there was a gradual decrease in the soil temperature, total hydrocarbon content and total organic carbon. The total petroleum hydrocarbon (TPH), oil and grease and polycyclic aromatic hydrocarbon (PAH) content showed statistical significance (p<0.05) compare to the control which implies that distances from the flare sites significantly influence the hydrocarbon parameters of the soil. From the molecular characterization of the bacterial isolates, the four isolates were Acinetobacter tandoii strain BASG143, Bacillus cereus strain Ou9, Bacillus subtilis strain BS3902 and Pseudomonas aeruginosa strain KAVKOI. These results show that these bacteria strains were able to degrade hydrocarbon contaminants.